Challenges of Gender Policy Implementation in the Security and Defense Sector - O. M. Tsukan; M. Yu. Burdin (Bulletin of Kharkiv National University of Internal Affairs)
The authors of the article have studied the problems of ensuring the principles of gender equality in the free trade sector of the security and defense sector. Aspects of gender equality have a special role in ensuring the educational process, managing the free economic zone and overcoming stereotyping of society, especially in the security and defense sector. It is extremely important to ensure the implementation of the principles of gender equality for the formation of a gender-neutral environment in the power sector of the state. This situation is possible only with the use of an integrated approach to equal opportunities for women and men to realize equal rights. The analysis of gender approaches used in free economic education with specific learning conditions on the example of Kharkiv National University of Internal Affairs made it possible to recommend to use best practices of international experience to accelerate the pace and quality of gender implementation at the University. The authors analyze all the activities of the University, which are aimed at ensuring the implementation of the principles of gender equality: institutional change, personnel component, academic disciplines, scientific and educational work of staff, projects, involvement of the international component.